Is Natural Population of Candida tropicalis Sexual, Parasexual, and/or Asexual? - Xu, Jianping (Frontiers in Cellular and Infection Microbiology, 2021)
Candida tropicalis is one of the most common opportunistic yeast pathogens of humans, especially prevalent in tropical and subtropical regions. This yeast has broad ecological distributions, can be found in both terrestrial and aquatic ecosystems, including being associated with a diversity of trees, animals, and humans. Evolutionary theory predicts that organisms thriving in diverse ecological niches likely have efficient mechanisms to generate genetic diversity in nature. Indeed, abundant genetic variations have been reported in natural populations (both environmental and clinical) of C. tropicalis. However, at present, our understanding on how genetic diversity is generated in natural C. tropicalis population remains controversial. In this paper, I review the current understanding on the potential modes of reproduction in C. tropicalis. I describe expectations of the three modes of reproduction (sexual, parasexual, and asexual) and compare them with the observed genotypic variations in natural populations. Though sexual and parasexual reproduction cannot be excluded, the analyses suggest asexual reproduction alone could explain all the observations reported so far. The results here have implications for understanding the evolution and epidemiology of C. tropicalis and other related human fungal pathogens.